Muslim world: its glorious past and today’s reality - Abdul Razak, Mohd Abbas; Salah, Machouche (Mission Soft Foundation, 2022)
In the distant past, the Muslim world was booming with new ideas in the areas of natural, social and revealed sciences. Muslim empires established many centres of learning and research for Muslims and others as well. The main epicentres for research and learning at that time were located in Baghdad, Cordoba, Damascus and Cairo. The Baitul Hikmah in Baghdad happened to be the largest library that housed many hundred thousand books. Experts in the ancient manuscripts among Muslims, Jews, Christians and Zoroastrians were recruited by the Abbasid rulers to teach, conduct research, and produce works of translation from Greek, Aramaic, Persian, Sanskrit and other ancient languages into Arabic.